Prevalence of Physical Inactivity and Sedentary Behavior Among Adults in Armenia - Tcymbal, Antonina; Andreasyan, Diana; Whiting, Stephen; Mikkelsen, Bente; Rakovac, Ivo; Breda, João (Frontiers in Public Health, 2020)
Physical inactivity and sedentary behavior are risk factors for developing non-communicable diseases. This study analyzed current levels of physical inactivity and sedentary behaviors among the adult population of Armenia. Data were collected through a national STEPS survey of non-communicable diseases risk factors on a nationally-representative sample of 2380 participants aged 18-69 years in Armenia in 2016. The Global Physical Activity Questionnaire was used to assess physical activity levels. Two out of ten people (21.6%) in Armenia did not meet the minimum levels of physical activity recommended by WHO to protect health. 13.2% of population spent over 8 hours per day sitting, 47.2% were inactive at work and 32.4% did not do any transport-related physical activity. Only 13.8% of participants were physically active during leisure time. Specific groups with relatively high levels of physical inactivity were older adults, residents of Yerevan, people with lower levels of education, the unemployed and people who were retired. Sedentary behavior was more common among men, students, people who were retired, unemployed, residents of Yerevan, and adults aged under 30 and over 45 years.